2003
DOI: 10.1046/j.1532-5415.2003.51453.x
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Mortality in 2,249 Nonagenarians—The Danish 1905‐Cohort Survey

Abstract: : In the oldest old, several known predictors of mortality, such as sociodemographic factors, smoking, and obesity, have lost their importance, but a high disability level, poor physical and cognitive performance, and self-rated health (women only), predict mortality, which shows that mortality in the oldest old is not a stochastic process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
232
6
11

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 238 publications
(280 citation statements)
references
References 38 publications
31
232
6
11
Order By: Relevance
“…those factors (among socio-demographic, physiological, clinical and haematochemical parameters) that are able to predict survival in the oldest old. On the whole, the survival analysis on the total Italian 90+ population demonstrated the longevity advantage of females, and it confirmed that factors often found to predict mortality in middle-aged and younger elderly, such as marital status, low education, blue collar type of occupation, smoking and every day alcohol intake, lost their importance at advanced ages, since they did not influence mortality (Nybo et al 2003). Moreover, it confirmed the predictive power of good physical ability (self-sufficiency for the basic ADL items), intact cognitive functioning (SMMSE test), positive self-rated health, absence of past myocardial infarction, BMI and hand grip strength over the median for future survival.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…those factors (among socio-demographic, physiological, clinical and haematochemical parameters) that are able to predict survival in the oldest old. On the whole, the survival analysis on the total Italian 90+ population demonstrated the longevity advantage of females, and it confirmed that factors often found to predict mortality in middle-aged and younger elderly, such as marital status, low education, blue collar type of occupation, smoking and every day alcohol intake, lost their importance at advanced ages, since they did not influence mortality (Nybo et al 2003). Moreover, it confirmed the predictive power of good physical ability (self-sufficiency for the basic ADL items), intact cognitive functioning (SMMSE test), positive self-rated health, absence of past myocardial infarction, BMI and hand grip strength over the median for future survival.…”
Section: Discussionsupporting
confidence: 62%
“…Therefore, given this increasing importance of the functional status as a predictor of survival, it is worth noting that, at an even more exceptional old age (after age 100), survival is mainly dependent on physiological reserve, physical and cognitive functions, as found in a study on Swedish centenarians (Hagberg and Samuelsson 2008). In spite previous studies showed that poor self-rated health was associated with increased mortality only in women (Nybo et al 2003), our results indicated that "excellent/good" self-reported health might be considered as one of the factors predicting survival in the oldest old, as found in more recent studies on old subjects from Calabria (Montesanto et al 2010) and from Denmark (Dato et al 2012). These data suggest the effectiveness of self-reported health, very simple to collect, as a surrogate measure of comorbidity and disability (Passarino et al 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first sample (the Danish 1905-Cohort) included 1,380 subjects aged 93 years (390 males and 990 females), recruited in the framework of a nationwide survey of all Danish people born in Denmark in 1905 (Nybo et al 2001;Nybo et al 2003;Christensen et al 2008). Briefly, 2,262 people participated initially in this survey which included a home-based interview aimed at the collection of socio-demographic information, evaluation of physical, cognitive, depressive status, sensory impairments, medications, selfreported health status, and blood sampling.…”
Section: Samplesmentioning
confidence: 99%
“…However, the association between alcohol consumption and survival is still largely unexplored among those aged 80 years and older. A study of nonagenarians (90+) did not find the J-or U-shaped association between alcohol and mortality, but results did indicate a higher mortality risk among abstainers compared to drinkers (Nybo et al, 2003). However, the health benefits of moderate alcohol consumption -at any age -is not uncontroversial (for a recent editorial, see Chikritzhs et al, 2015), and alcohol abstinence, particularly in old age, is often due to underlying health problems that constrain alcohol consumption.…”
Section: Introductionmentioning
confidence: 99%